Use of Voice and Music Making Among Six-Year Old Foochow Children in Sarikei, Sarawak, Malaysia - Wong, Annie Kai Sze (2011)
This study describes comprehensively the musical characteristics of the Sarikei’s Foochow children in relation to the cultural environment in which they live. The description of music characteristics covers the aspects of the use of voice, rhythm and singing languages. Methodology used in this study is ethnographical fieldwork which includes structural and casual observation of children’s music learning process supplemented by dialogues with the teachers and parents. The use of voice of the Foochow children takes place in the form of singing, game and voice exclamation, which can be further divided as the singings of familiar, modified and self composed song, imitation of sound, verbal prescription of movements, emotional expression, and, the exploration of voice colors. The ubiquitous interplay between children’s speech and the voice play resembles the strong influence of the Foochow dialect, which can be observed in many instances like the use of onomatopoeia, Foochowized intonation of certain terms, exclamation syllabus of certain words, among others. The use of rhythm of Sarikei Foochow children, on the other hand, is observed in their number counting, vocabulary chanting, general activities in their kindergarten, as well as in their games. The structural features in the use of rhythm such as head emphasis, extension of end syllabus, and, the even distribution of duration, are consistently observed; which suggests its close relation to the rhythmic features of Southern Chinese dialects in general. Observation on the use of different singing languages which are Malay, English, Mandarin and Foochow revealed that children singing in familiar languages are found to be able to memorize the text faster, were more motivated to learn, and had higher level of concentration. The use of Foochow dialect, their mother tongue, has given a remarkable impact on the children’s motivation and behavior in singing, which surpassed their musical responsiveness when other languages were used. The outcome of study showed that linguistic environment, religion, lifestyle, and family influence contributed to children’s development of musicality and creativity. Further study could involve other dialect groups of the Chinese communities in Malaysia to further explicate the many ways cultural environment shapes the musicality of a child.